From Expectations to Experiences: Consumer Autonomy and Choice in Personal Genomic Testing. Issue 1 (2nd January 2020) - Savard, Jacqueline; Hickerton, Chriselle; Metcalfe, Sylvia A.; Gaff, Clara; Middleton, Anna; Newson, Ainsley J.
Abstract: Background: Personal genomic testing (PGT) offers individuals genetic information about relationships, wellness, sporting ability, and health. PGT is increasingly accessible online, including in emerging markets such as Australia. Little is known about what consumers expect from these tests and whether their reflections on testing resonate with bioethics concepts such as autonomy. Methods: We report findings from focus groups and semi-structured interviews that explored attitudes to and experiences of PGT. Focus group participants had little experience with PGT, while interview participants had undergone testing. Recordings were transcribed and analyzed using thematic analysis. Findings were critically interpreted with reference to bioethics scholarship on autonomy. Results: Fifty-six members of the public participated in seven focus groups, and 40 individuals were interviewed separately. Both groups valued the choice of PGT, and believed that it could motivate relevant actions. Focus group themes centered on the perceived value of choices, knowledge enabling action and knowledge about the self. Interview themes suggest that participants reflexively engage with their PGT information to make meaning, and that some appreciate its shortcomings. Critical interpretation of findings shows that while consumers of PGT are able to exercise a degree of autonomy in choosing, they may not be able to achieve a substantive conceptualization of autonomy, one that promotes alignment with higher-order desires. Conclusions: PGT consumers can critically reason about testing. However, they may uncritically accept test results, may not appreciate drawbacks of increased choice, or may overestimate the potential for information to motivate behavioral change. While consumers appear to be capable of substantive autonomy, they do so without ongoing support from companies. PGT companies promote a problematic ("default") account of autonomy, reliant on empowerment rhetoric. This leaves consumers vulnerable to making decisions inconsistent with their higher-order desires. As PGT expands, claims about its power and value need to be carefully drawn.